Paper card-like electrochemical platform as a smart point-of-care device for reagent-free glucose measurement in tears. Issue 29 (17th March 2023) - Fiore, Luca; Sinha, Ankita; Seddaoui, Narjiss; di Biasio, Jessica; Ricci, Federico; Stojanovic, Goran M.; Arduini, Fabiana
Abstract : A novel paper card-like acting like a credit card to be inserted into a reusable polyvinyl chloride electrochemical fluidic system for furnishing all the reagents required for glucose measurement in artificial tears. Abstract : This communication describes the development of polyvinyl chloride electrochemical system in which a paper layer loaded with reagents is inserted into the device, demonstrating a new concept of a paper card-like pad for a reagent-free and easy measurement of the target analyte in solution. This device detects glucose in artificial tears in the range of 0.2–2 mM with a detection limit of 50 μM by simply adding the artificial tears to the paper card-like pad. The novel configuration goes beyond the state of the art, widening the application range of paper in the design of smart analytical devices.